2016
DOI: 10.1016/j.jphotobiol.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and skin: Friend or foe

Abstract: In the last decade, it has been proposed that the sun's IR-A wavelengths might be deleterious to human skin and that sunscreens, in addition to their desired effect to protect against UV-B and UV-A, should also protect against IR-A (and perhaps even visible light). Several studies showed that NIR may damage skin collagen content via an increase in MMP-1 activity in the same manner as is known for UVR. Unfortunately, the artificial NIR light sources used in such studies were not representative of the solar irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
183
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(193 citation statements)
references
References 53 publications
1
183
0
9
Order By: Relevance
“…It is suggested that fibroblast growth factor (FGF) stimulation leads to the reactivation of ERK signaling [12]. This has been most observed for the treatment of acne, as the photobiomodulation (PBM) effect is associated with increased proliferation of extracellular matrix (ECM) components and gene expression of anti-inflammatory cytokines [13]. The ECM cells, such as fibroblasts and macrophages, produce growth factors, cytokines, and chemokines crucial for regeneration and repair [14].…”
Section: Mechanisms Of Pdt At Low Levels Of Energymentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that fibroblast growth factor (FGF) stimulation leads to the reactivation of ERK signaling [12]. This has been most observed for the treatment of acne, as the photobiomodulation (PBM) effect is associated with increased proliferation of extracellular matrix (ECM) components and gene expression of anti-inflammatory cytokines [13]. The ECM cells, such as fibroblasts and macrophages, produce growth factors, cytokines, and chemokines crucial for regeneration and repair [14].…”
Section: Mechanisms Of Pdt At Low Levels Of Energymentioning
confidence: 99%
“…NF-kB is then transported to the nucleus and cause the expression of approximately 150 genes possibly involved in defense mechanisms against cell stress. Therefore, the concentration of ROS may contribute to benefit cells proliferation or be cytotoxic [13,15]. The NF-kB activation can also be stimulated by ROS in other situations involving tumor necrosis factor alpha (TNFa), phorbol ester, and interleukin (IL)-1 [15].…”
Section: Mechanisms Of Pdt At Low Levels Of Energymentioning
confidence: 99%
See 1 more Smart Citation
“…CSR1 or CSR2 = CSO1 or CSO2 + e - (6) CSR1 or CSR2 + GS(H 4 O) = GS + H 4 O -+ CSO1 or CSO2 + GS (7) CSR1 or CSR2 + GS + H + = GSH + H 4 O -+ CSO1 or CSO2 (8) TOSH regeneration of CSR2 from CSO2 could occur as follows:…”
Section: Complex System Dynamics Between Photons Tosh Dna Glutathimentioning
confidence: 99%
“…No such TOSH structure rupturing appears to occur under VIS Red, Middle Infrared (MIR) or Far Infrared (FIR) light (Oehr and LeMay 2014;Chai et al 2009). To gain a clearer perspective on where these respective wavelengths fall within the light spectrum, see Figure 2 (source: Barolet et al 2016. ) Depending on the wavelength of light involved, most drops in ambient photonic inputs generally result in concomitant drop in the charge divergent EZ fi elds fed by the absorption of this light.…”
Section: Introductionmentioning
confidence: 99%